Thermodynamic assessment of the CaO–P2O5–SiO2–ZnO system with special emphasis on the addition of ZnO to the Ca2SiO4–Ca3P2O8 phase. (December 2019) - Jantzen, Tatjana; Yazhenskikh, Elena; Hack, Klaus; Müller, Michael
Abstract: The CaO–P2 O5 –SiO2 –ZnO system including all binary and ternary sub-systems has been thermodynamically assessed using all available experimental data. Particular attention was given to the phase C2S–C3P which forms a complete solid solution with end-members α-Ca2 SiO4 and α′-Ca3 P2 O8 . In addition, the present modelling of the phase C2S–C3P allows the inclusion of experimentally determined solubility values of zinc oxide in both end-members of the phase C2S–C3P. The mutual solubility between different crystallographic modifications of calcium and zinc phosphates is also described in this work using available experimental data. 24 phospates as stoichiometric phases have also been included in the database. Highlights: CaO–P2 O5 –SiO2 –ZnO system thermodynamically assessed. Binary and ternary systems considered. Modified associate species model used for the liquid phase. 9 solid solutions introduced using the multi-sublattice approach. Calculated phase diagrams and thermodynamic properties in good agreement with the experimental data.